Effect of Organizational Climate and Motivation on Employee Performance PT. Al-Amsor Wisata Mubarokah Banjarmasin - Irwansyah Irwansyah; Sulastini Sulastini; Hairudinor Hairudinor (Universitas Lambung Mangkurat, 2014)
The purpose of this study was to (1) examine the effect of organizational climate on employee performance, (2) examine the effect of motivation on employee performance, (3) examine the effect of organizational climate and motivation simultaneously on the performance of employees of PT. Al-Amsor Mubarokah Wisata Banjarmasin.The research uses a quantitative approach to causal associative type. The unit of analysis is the entire employees of PT. Al-Amsor Mubarokah Wisata Banjarmasin totaling 180 people. Sample set at 108 or at 65% of the total population selected using random sampling techniques Stratifield Nonproportionate. To test pengrauh between variables used multiple linear regression.The research results prove: (1) there is no significant effect of partial organizational climate on employee performance PT. Al-Amsor Mubarokah Wisata Banjarmasin, (2) There is a significant effect on the performance of partial motivation of employees of PT. Al-Amsor Mubarokah Wisata Banjarmasin, (3) There is no significant effect of simultaneous organizational climate to employee performance PT. Al-Amsor Mubarokah Wisata Banjarmasin. The influence of motivation on performance is 79.9%, while the influence was 62.8% simultaneously. Keywords: organizationalclimate, motivation, Performance